Nd doping effect on Bi1−xNdxFe0.97Co0.03O3 thin films: Microstructural, electrical, optical and enhanced multiferroic properties - Xue, Xu; Tan, Guoqiang; Liu, Wenlong; Ren, Huijun (Materials chemistry and physics, 2014)
Multiferroic Bi1−xNdxFe0.97Co0.03O3 (BNFCO) thin films with compositions x = 0.06, 0.09, 0.12, and 0.15 were deposited on fluorine-doped SnO2 substrates. The microstructure, chemical state, leakage mechanism, ferroelectric and magnetic properties were investigated. XRD analysis and Raman scattering spectra reveal that Nd doping gives rise to a triclinic structure transition for BNFCO films with respect to the original rhombohedral structure of BFO film. XPS analysis shows that the number of unoccupied states in the Bi 5d and Fe 3d orbits are increased with the increase of Nd content, which probably demonstrates a Fe/Bi-to-Nd electron transfer process. Fowler–Nordheim tunneling conduction mechanism associated with oxygen vacancies is responsible for the low breakdown voltage of BFO. The leakage mechanism of BNFCO is subject to trap-free Ohmic conduction due to the high bond strength among the Bi, O and Fe ions and the low concentration of oxygen vacancies, therefore, improves the resistivity in the high electric field. Highly enhanced ferroelectric properties with giant remanent polarization of 107.5 μC cm−2 is obtained via 15% Nd doping. The magnetic property is also increased by Nd doping, which is ascribed to the modified spiral spin structure and the small grain size effect. The band gap values of the BNFCO films are gradually decreased with the increase of Nd content. •Nd doping gives rise to triclinic structure transition for BNFCO.•BNFCO shows the coexistence of ferroelectricity and magnetism at RT.•The bond strength of BNFCO is increased with the increase in Nd content.•Leakage currents of BNFCO are found to be subject to trap-free Ohmic conduction.•The band gap of BNFCO is decreased with the increase in Nd content.